Análisis de conceptos audiovisuales del video musical Firstman de Camila Cabello - Campos Troya, Omaira Julissa (2023)
The case study develops an analysis of audiovisual concepts of the music video "First Man" by Camila Cabello, thanks to the help of interviews with two experts in audiovisual production, where the points of view on what is involved in the creation of a music video will be evidenced. The music video is an audiovisual and artistic expression where the creator transmits emotions to his audience. The results show that a music video has key processes to achieve a good production such as colorization, narrative, editing and editing. With the analysis sheet we observe in detail each of its components to have a better visualization and understanding.